The use of electronic cigarette on young adults: Curiosity, dependency or fad? (Research, Society and Development, 2023)
The aim was to analyze a compilation of scientific articles dealing with electronic nicotine delivery systems, which have been observed to be on the rise among young adults. In this way, there was an association with the perception that they are less harmful than combustible cigarettes, in addition, there is a curiosity in their use, a marketing with positive perceptions and social acceptance around these devices. The methodology used was an integrative literature review based on the data contained in the Virtual Health Library, where the following descriptors were used: "Electronic Nicotine Delivery Systems", "Adolescent" and "Young Adult". In all, after selecting the filters, 1,003 journals were found and, following the inclusion and exclusion criteria, 10 articles were selected. The results obtained indicate that international studies make up the majority of the theoretical framework used, with a focus on the harmful effects of using electronic cigarettes. It was observed that electronic nicotine delivery systems have grown in popularity internationally in the last decade, and that young adults believe that they provide a safer and more enjoyable alternative to "smoking", but there is growing evidence that they cannot be considered harmless devices, since they bring harm to the systems of the human body.